Geochemical characteristics and hydrocarbon expulsion of source rocks in the first member of the Qingshankou Formation in the Qijia‐Gulong Sag, Songliao Basin, Northeast China: Evaluation of shale oil resource potential. Issue 5 (9th January 2020) - Huo, Zhipeng; Hao, Shibo; Liu, Bo; Zhang, Jinchuan; Ding, Jianghui; Tang, Xuan; Li, Changrong; Yu, Xiaofei
Abstract: In recent years, there has been significant progress in shale oil exploration in the first member of the Qingshankou Formation (K2 qn 1 ) in the Qijia‐Gulong Sag, Songliao Basin, Northeast China: It shows good prospects for shale oil. However, the recognized lack of the geochemical and hydrocarbon generation and expulsion characteristics of K2 qn 1 source rocks limits an accurate evaluation of shale oil resource. This study systematically investigated the geological and geochemical characteristics, hydrocarbon generation and expulsion, and shale oil potential of the K2 qn 1 source rocks. The results show that the K2 qn 1 mudstones were mainly deposited in the semideep and deep lacustrine facies under reducing and weak reducing conditions. Compared with the southern Gulong Sag, the northern Qijia Sag has a higher salinity, more abundant prosperous aquatic organisms, and a greater paleoproductivity. The K2 qn 1 source rocks are pervasive and continuous in the entire sag, with maximum thicknesses greater than 110 m. They have a higher organic matter (OM) abundance (2.40% of the average TOC), are dominated by type I and II1 kerogen, and are mature (0.8%‐0.1.3% VR ), which indicate that they are good to excellent source rocks and have significant hydrocarbon generation potential. The source rocks in the Qijia Sag have a higher OM abundance, a better OM type, and a lower OM maturity than those in the Gulong Sag. The threshold and peak hydrocarbon expulsion values for marlstone source rocks are 0.85% VR and 0.95% VR, respectively. The volumes of hydrocarbons generated and expulsed from the K2 qn 1 source rocks are 121.8 × 10 8 t and 46.9 × 10 8 t, respectively, with a retention efficiency of 61.5%. The in‐place and recoverable resources of shale oil are 74.9 × 10 8 t and (12.0‐13.5) × 10 8 t, respectively, indicating that the entire sag has a significant shale oil potential, especially the Qijia Sag. Abstract : Organic‐rich mudstones of K2 qn 1 were deposited in semideep and deep lake facies with reducing and weak reducing conditions, and high TOC, type I and type II1 kerogen and are mature. The threshold and peak of hydrocarbon expulsion of K2 qn 1 source rocks are at 0.85% VR and 95% VR, respectively. The shale oil resource is 74.9 × 10 8 t, indicating a significant exploration potential.